ANALYSING NOVEL TRANSLATION: The Equivalence of Meaning and Style - Masduki, Masduki (Universitas Muhammadiyah Surakarta, 2011)
The analysis of the process of translating a novel needs to be holistically approached which refers to the examination of translation in the viewpoints of genetic factor, objective factor, and affective factor. This analysis is conducted based on the consideration that there is an interplay between translators as the mediating agents, processes of translation, products of translation, and the opinion of the readers about the products of translation. This article highlights the current result of the research conducted by the writer focusing on the analysis on the equivalence of meaning and style found in an Indonesian translation of an English novel using the holistic criticism approach.Key words: Equivalence, Meaning, Style, Holistic Approach